2018
DOI: 10.1039/c7ce02103h
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of indium into ε-gallium oxide epitaxial thin films grown via mist chemical vapour deposition for bandgap engineering

Abstract: Epitaxial ε-gallium oxide (Ga2O3) thin films incorporated with In were successfully grown by mist chemical vapour deposition (CVD) on c-plane sapphire substrates for bandgap tuning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 38 publications
3
58
0
Order By: Relevance
“…This was recently confirmed by Leone et al, who reported on the epitaxial growth of GaN/ Ga 2 O 3 and e-Ga 2 O 3 /GaN heterostructures for novel high electron mobility transistors. 18 e-Ga 2 O 3 alloys with In and Al were obtained with mist Chemical Vapor Deposition (mist-CVD) and Pulsed Laser Deposition (PLD), 19,20 while a theoretical study 21 demonstrated the possibility to form a 2D electron gas at the e-AlGaO 3 / e-Ga 2 O 3 heterointerface with higher carrier density with respect to b-Ga 2 O 3 and the effect of spontaneous polarization reversal on the 2D electron gas density in e-Ga 2 O 3 /e-AlGaO 3 /e-Ga 2 O 3 double heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…This was recently confirmed by Leone et al, who reported on the epitaxial growth of GaN/ Ga 2 O 3 and e-Ga 2 O 3 /GaN heterostructures for novel high electron mobility transistors. 18 e-Ga 2 O 3 alloys with In and Al were obtained with mist Chemical Vapor Deposition (mist-CVD) and Pulsed Laser Deposition (PLD), 19,20 while a theoretical study 21 demonstrated the possibility to form a 2D electron gas at the e-AlGaO 3 / e-Ga 2 O 3 heterointerface with higher carrier density with respect to b-Ga 2 O 3 and the effect of spontaneous polarization reversal on the 2D electron gas density in e-Ga 2 O 3 /e-AlGaO 3 /e-Ga 2 O 3 double heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…31 . Featuring even larger polarization differences, the incorporation of In 32 or Al 33 into κ − Ga 2 O 3 enabled bandgap tuning between 4.25 and 6.2 eV 34 and is expected to enable 2DEGs with even higher sheet carrier densities. The κ phase was found to thermally transition to β only under annealing at high temperatures T > 700 − 800 • C, 14,35 allowing for applications in devices requiring sufficiently high working temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The κ phase was found to thermally transition to β only under annealing at high temperatures T > 700 − 800 • C, 14,35 allowing for applications in devices requiring sufficiently high working temperatures. To date, the orthorhombic phase has been grown successfully 36 on a number of different substrates, including Al 2 O 3 (0001), GaN (0001), AlN (0001), 6H-SiC or β -Ga 2 O 3 (201), using halide vapour phase epitaxy, 14,37,38 atomic layer deposition, 39 metal-organic chemical vapor deposition, 15,18,22,27,30,35,37,[39][40][41][42][43][44] metal-organic vapor phase epitaxy, 1,[45][46][47][48] mist CVD 16,17,32,33,49,50 , plasma-assisted molecular beam epitaxy 51,52 , laser molecular beam epitaxy, 21,53 and pulsed laser deposition 12,13,24,[54][55][56][57] .…”
Section: Introductionmentioning
confidence: 99%
“…κ-Ga2normalO3 can be grown heteroepitaxially by several deposition methods, such as pulsed‐laser deposition [ 14,19–26 ] (PLD), halide vapor phase epitaxy [ 18,27–29 ] (HVPE), metal‐organic chemical vapor deposition [ 17,30–35 ] (MOCVD), metal‐organic vapor phase epitaxy [ 36–39 ] (MOVPE), atomic layer deposition, [ 31 ] molecular beam epitaxy [ 40 ] (MBE), plasma‐assisted molecular beam epitaxy [ 41 ] (PAMBE), and mist CVD. [ 15,16,42–49 ]…”
Section: Introductionmentioning
confidence: 99%
“…Research on the In as well as Al alloy systems of the κ ‐phase is still relatively scarce, as up to now only reports on PLD [ 23–25,50,51 ] as well as mist CVD [ 16,44 ] growth are available. However, these alloys can be grown phase pure in a broad composition range [ 23–25,50 ] of xIn0.35 and xAl0.65.…”
Section: Introductionmentioning
confidence: 99%